2016
DOI: 10.1111/hel.12348
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐3178 ameliorates inflammation and gastric carcinogenesis promoted by Helicobacter pylori new toxin, Tip‐α, by targeting TRAF3

Abstract: Taken all together, Tip-α might activate NF-κB to promote inflammation and carcinogenesis by inhibiting miR-3178 expression, which directly targeting TRAF3, during H. pylori infection in gastric mucosal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
(90 reference statements)
0
24
0
Order By: Relevance
“…It makes up one of the potential markers of H. pylori virulence [164,165]. By combining with the nucleolin receptor, Tipα induces mesenchymal changes of cells via EMT progression [166][167][168]. Tipα, as a carcinogenic factor, activates NF-κB, promoting gastric carcinogenesis by inhibiting miR-3178 expression [169,170].…”
Section: Tumor Necrosis Factor α-Inducing Protein Of H Pylori In Emtmentioning
confidence: 99%
“…It makes up one of the potential markers of H. pylori virulence [164,165]. By combining with the nucleolin receptor, Tipα induces mesenchymal changes of cells via EMT progression [166][167][168]. Tipα, as a carcinogenic factor, activates NF-κB, promoting gastric carcinogenesis by inhibiting miR-3178 expression [169,170].…”
Section: Tumor Necrosis Factor α-Inducing Protein Of H Pylori In Emtmentioning
confidence: 99%
“…Regarding H. pylori ‐related virulence factors, Zou et al. demonstrated that Tip‐α, a carcinogenic factor of H. pylori , activated NF‐κB by inhibiting the miR‐3178‐mediated targeting of TRAF3 . MiR‐124 has tumor suppressive functions and is regulated by CpG methylation silencing .…”
Section: Deregulation Of Host Functionsmentioning
confidence: 99%
“…46 Regarding H. pylori-related virulence factors, Zou et al demonstrated that Tipα, a carcinogenic factor of H. pylori, activated NF-κB by inhibiting the miR-3178-mediated targeting of TRAF3. 47 MiR-124 has tumor suppressive functions and is regulated by CpG methylation silencing. 48 Murray-Stewart et al reported that miR-124 is a negative regulator of polyamine catabolic enzyme spermine oxidase (SMOX), which is induced in H. pylori gastritis.…”
Section: H Pylori Infection and Autophagymentioning
confidence: 99%
“…They concluded that miRNAs modulate mucosal cytokine expression and are involved in regulating gastric pathology. Zou et al . found that miR‐3178 was decreased in H. pylori‐ infected human gastric tissue, and investigated its role in regulating the inflammatory response to tumor necrosis factor‐α‐inducing protein (Tip‐α), a recently identified H. pylori toxin.…”
Section: Inflammationmentioning
confidence: 99%
“…Zou et al 15 found that miR-3178 was decreased in H. pylori-infected human gastric tissue, and investigated its role in regulating the inflammatory response to tumor necrosis factorα-inducing protein (Tipα), a recently identified H. pylori toxin. Addition of rTipα to GECs, resulted in increased TNFα and IL-6 expressions.…”
Section: Epithelial Cell -Helicobacter Pylori Interactionsmentioning
confidence: 99%